Immunogenetic effects of low dose (CEM43 30) magnetic nanoparticle hyperthermia and radiation in melanoma cells. (29th November 2019) - Duval, Kayla E. A.; Vernice, Nicholas A.; Wagner, Robert J.; Fiering, Steven N.; Petryk, James D.; Lowry, Gabriela J.; Tau, Steven S.; Yin, John; Houde, Georgia R.; Chaudhry, Aneeq S.; Hoopes, P. Jack
Abstract: Objective: In this in vitro study we have used an RNA quantification technique, nanoString, and a conventional protein analysis technique (Western Blot) to assess the genetic and protein expression of B16 murine melanoma cells following a modest magnetic nanoparticle hyperthermia (mNPH) dose equivalent to 30 minutes @ 43°C (CEM43 30) and/or a clinically relevant 8 Gy radiation dose. Methods: Melanoma cells with mNPs(2.5 μg Fe/106 cells) were pelleted and exposed to an alternating magnetic field (AMF) to generate the targeted thermal dose. Thermal dose was accurately monitored by a fiber optic probe and automatically maintained at CEM43 30. All cells were harvested 24 hours after treatment. Results: The mNPH dose demonstrated notable elevations in the thermotolerance/immunogenic HSP70 gene and a number of chemoattractant and toll-like receptor gene pathways. The 8 Gy dose also upregulated a number of important immune and cytotoxic genetic and protein pathways. However, the mNPH/radiation combination was the most effective stimulator of a wide variety of immune and cytotoxic genes including HSP70, cancer regulating chemokines CXCL10, CXCL11, the T-cell trafficking chemokine CXCR3, innate immune activators TLR3, TLR4, the MDM2 and mTOR negative regulator of p53, the pro-apoptotic protein PUMA, and the cell death receptor Fas. Importantly a number of the genetic changes were accurately validated by protein expression changes, i.e., HSP70, p-mTOR, p-MDM2. Conclusion: These results not only show that low dose mNPH and radiation independently increase the expression of important immune and cytotoxic genes but that the effect is greatly enhanced when they are used in combination.